Deusi Bhailo: Cultural Traditions and the Impact of Modern Financial Aspects - Sharma, Santoshi; Sharma, Monika; Adhikari, Swastika (Journal of Multidisciplinary Research Advancements, 2025)
This study examines the evolving dynamics of Deusi Bhailo, a traditional Nepali cultural practice performed during the Tihar festival, with a focus on the tension between cultural preservation and financial motivations. Using a mixed-methods approach combining qualitative interviews (n=30) and quantitative surveys (n=50) with participants stratified by age (children, adults, elders) in Gaindakot-1, the research reveals a generational divide: while 41.7% of youth (12–16 years) prioritize financial aspects, 42.1% of elders (60+ years) emphasize cultural significance, with adults (23–40 years) mediating between these perspectives (40% cultural vs. 25% financial). Findings highlight the tradition’s "hybrid" evolution, with modern adaptations coexisting alongside enduring ritual elements. Key challenges include the risk of over-commercialisation and fragmented intergenerational transmission. The study proposes three preservation strategies: school-based cultural education, hybrid performances that blend folk and modern elements, and community guidelines for ethical monetisation. These findings contribute to global discourse on safeguarding intangible heritage amid socioeconomic change, offering a model for balancing tradition and modernity.